Study on the effect of COVID − 19 pandemic on the savings and investment pattern of the manufacturing sector. (2022) - Rose Nirmala, Annie; Bhalaji, R.K.A.; Bharani Kumar, S.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: As a consequence of Corona Virus unroll; humans faced uncertainty in income and changes in lifestyle. Due to lockdown, the spending attitude changed, as there was no way to have outings, expensive purchases like gold, real estate, car, etc. Most of the decisions are based on the circumstances faced. The circumstances are like walls, putting a limit around us. Behavioural Finance shows the financial activity of an individual based on his or her mental stability. In this paper, the savings and investment decisions before and after the COVID − 19 pandemic of the people related to the manufacturing sector in Tamil Nadu are observed by a survey. A study was made on circumstances created by COVID − 19 pandemic which brought change in savings behaviour and investment behaviour of individuals in manufacturing sector. An analysis was made based on the survey conducted to know the impression of the pandemic on manufacturing sector peoples' financial attitudes in Tamil Nadu (TN). The participants belonged to the working community of manufacturing sector. The association between the circumstances formed by corona virus and change in savings and investment options of the people related to the manufacturing sector in Tamil Nadu was studied. There is association between the actions undertaken by the Government (like lockdown and travel restrictions) and person's earnings, directly impacted savings and investment pattern of the individuals in manufacturing sector.